Important preoperative prognostic factors for extracapsular extension, seminal vesicle invasion and lymph node involvement in cases with radical retropubic prostatectomy - (:unkn) unknown (My University, 2004)
Introduction: Initial diagnostic evaluation may provide information about the extent of disease after radical retropubic prostatectomy (RRP). The aim of this study was to investigate the predictive value of preoperative serum prostate specific antigen (PSA) level, local disease extension identified by transrectal ultrasound (TRUS), total number of positive biopsies and percentage of positive cores for cancer, as well as TRUS Biopsy Gleason score in determining the extent of disease in radical retropubic prostatectomy specimens. Materials and methods: A retrospective analysis was performed on 171 patients who underwent RRP from March 1993 to February 2003 for organ confined prostate cancer and whose follow-up data was accessible. The correlation of preoperative serum PSA level, local disease extension in TRUS, the total number of positive sextant biopsies and the percent of cores positive for cancer and Gleason score at TRUS biopsy specimen with the extent of disease at final pathology (Extra-capsular extension (ECE), seminal vesicle invasion (SVI), lymph node involvement (LNI) and surgical margin (SM) status on RRP specimens) were analyzed. Results: The median age of the patients was 65 years. The mean preoperative serum PSA level of all patients was 11.6 ± 1.2 (median 8.6) ng/ml. Histopathological evaluation of RRP specimens revealed 60 (35%) patients with ECE, 38 (22.2%) with SVI, 7 (0.04%) with LNI, and 58 (33.9%) had positive SM. Comparing the preoperative TRUS findings and postoperative evaluation of RRP specimens, the sensitivity of TRUS in predicting the ECE was 11.8% and specificity was 96%. Sensitivity of TRUS in predicting SVI was 9.8% and its specificity was 99%. With univariate analysis (sample t -test), Gleason score, percent of cores positive for cancer, and DRE were found to be predictive factors for extra-prostatic disease in RRP specimens. But with multivariate analysis (logistic regression test) Gleason score appears to be the most important and independent predictive factor for extra-prostatic disease in RRP specimens. Serum PSA levels and percentages of cores positive for cancer were also significant predictors of non organ-confined disease found at final pathology. Conclusion: Gleason score is the most important and independent predictive factor for extra-prostatic disease. Serum PSA levels and percentages of cores positive for cancer are the other important but non-independent predictive factors. © 2004 Kluwer Academic Publishers.
Keywords: Biopsy; Gleason score; Prostate neoplasm